Implementasi Pendekatan Child-Centered Learning dalam Pengembangan Pembelajaran Pendidikan Anak Usia Dini (PAUD) - Nur Azizah; Aris Suziman (FKIP UNSULTRA, 2026)
The child-centered learning approach is a pedagogical strategy that positions children as the central subjects in the learning process. This study aims to examine the concept, principles, and implementation of the child-centered learning approach in Early Childhood Education (PAUD). The method used is a literature review by analyzing various sources such as scientific journals, books, and documents related to early childhood education. This study specifically focuses on the implementation of the child-centered learning approach in the development of learning in Early Childhood Education (PAUD). The results of the study indicate that this approach provides opportunities for children to actively explore the environment, develop creativity, and build knowledge based on direct experience. Teachers act as facilitators who support children's needs and interests. In addition, child-centered learning can also improve aspects of holistic development, including cognitive, social-emotional, language, and motor skills. However, its implementation still faces several challenges such as limited teacher understanding, inadequate facilities, and a less-than-ideal teacher-to-child ratio. Therefore, ongoing training for educators and support from various parties are needed to optimize the implementation of this approach. In conclusion, child-centered learning is an effective approach in improving the quality of learning in PAUD because it provides space for children to develop according to their potential and characteristics.